PERAN GURU DALAM MENGENALKAN SAINS PADA ANAK USIA DINI - Wilma Rahmah Hidayati; Dadan Suryana; Hulailah Istiqlaliyah . (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2021)
This study aims to find out the role of educators in introducing science to early childhood.Educators are the most important aspect of education in school. But the reality in the field there are still many teachers who are not ready in designing a creative activity.Teachers still have difficulty in teaching children science learning.and looking for science activities for children. This research uses literature study method whose data comes from journals, articles, books from the results of reading, recording and analyzing in accordance with existing problems. The results and discussion in this research is to carry out the learning process, it is necessary to design learning (RPPH) in accordance with children's cognitive development regarding the development of science, determining the tools and materials to be used.The implementation is also regrettable with the planning and carried out while playing and learning, as well as conducting assessments with reference to STPPA.The conclusion is that the teacher's efforts in introducing science can be started from the design of learning, implementation, and assessment and activities carried out is a fun activity and carried out while playing.